Adolescents with chronic health conditions in transition of care: needs and support - Alanen, Anna (fi=Turun yliopisto|en=University of Turku|, 2025)
To ensure that adolescents with chronic health conditions have continuous high-quality care, it is vital that their process of transition from paediatric to adult healthcare is constantly assessed and improved. Addressing adolescents’ medical and psychosocial needs may lead to better health outcomes and a smooth transition to adult healthcare. This thesis aimed to evaluate the healthcare needs and the support of adolescents aged 15-24 years with chronic health conditions across the transfer of care. Data were gathered through surveys across the transfer of care at three stages: at the children’s hospitals; one year; and two years, after the transfer of care in Finland and Australia. This study was comprised of four studies; a cross-sectional study, two longitudinal studies and a systematic review. The cross-sectional study explored the healthcare needs related to associations of age, transition readiness with care-related anxiety of adolescents (n = 512). It also compared adolescents’ and their parents’ perceptions of transition readiness and health self-management (n = 322). The first longitudinal study with data gathered before and after the transfer of care (adolescents n = 440), also focused on healthcare needs: (changes in anxiety; care experiences; and the impact of chronic health conditions; and their associations with each other). The second longitudinal study examined healthcare support related to psychosocial aspects of care and the use of secure digital health services among the Finnish participants at three time points (n = 163). Finally, a systematic review described digital transition interventions with health coaching elements developed for adolescents with chronic health conditions. The results of this study suggested that good health knowledge and positive health behaviour may be associated with lower care-related anxiety levels at the children’s hospital. High condition impact and negative care experiences were associated with higher levels of care-related anxiety across the transfer of care. Time alone with doctors and discussions on confidentiality were at a suboptimal level across the transfer of care. Focusing on confidentiality and person-centred care may help to identify adolescents in the highest need of support. Digital health interventions need to be well-integrated into care, easy to use, personalised, and show potential to engage and motivate health self-management among adolescents. To conclude, the results strengthen the understanding that tailored transition interventions, starting at 12 years of age, which encompass psychosocial aspects and goal-driven care, may improve transitional care. The results reflect the different dimensions of person-centred care, comprising measures on; self-reported condition impact; care experiences; care-related anxiety; transition readiness; and psychosocial discussions. Digital interventions as part of usual care may provide chronically ill adolescents with efficient and accessible care. Health coaching shows positive results and may be integral to future digital healthcare. KEYWORDS: adolescents, chronic conditions, transition, transition readiness, digital health services, anxiety, psychosocial assessment, health coaching

Pitkäaikaissairaiden nuorten hoidon siirtymävaiheen kehittäminen ja arviointi ovat tärkeitä jatkuvan ja laadukkaan hoidon varmistamiseksi. Nuorten hoidon ja psykososiaalisen tuen tarpeen huomioiminen voivat johtaa parempiin terveystuloksiin ja sujuvampaan siirtymiseen aikuisten terveydenhuollon palveluihin. Tässä väitöskirjassa arvioidaan pitkäaikaissairaiden 15–24-vuotiaiden nuorten tervey-denhuollon tarpeita ja saatavilla olevaa tukea hoidon siirtyessä lasten sairaalasta aikuisten terveydenhuollon palveluihin. Aineisto kerättiin kyselytutkimuksella Suomessa ja Australiassa kolmessa eri ajankohdassa: lastensairaalassa, vuosi ja kaksi vuotta siirtymän jälkeen. Tutkimus koostui neljästä osasta: poikkileikkaustutkimus, kaksi pitkittäistutkimusta ja systemaattinen katsaus. Poikkileikkaustutkimuksessa tarkasteltiin nuorten (n= 512) hoidon tarpeita: (iän, siirtymävalmiuden ja hoitoon liittyvän ahdistuksen yhteyksiä) sekä vertailtiin nuorten ja heidän vanhempiensa (n= 322) näkemyksiä siirtymävalmiudesta ja itsehoidosta. Pitkittäistutkimuksessa vertailtiin muutoksia nuorten (n= 440) tarpeissa (hoitoon liittyvässä ahdistuneisuudessa, hoitokokemuksissa ja sairauden koetussa vaikutuksessa elämään sekä näiden välisiä yhteyksiä hoidon siirtymän aikana). Toinen pitkittäistutkimus tarkasteli suomalaisten osallistujien saamaa terveydenhuollon hoidon tuen muotoja (psykososiaalisen tuen arviointia ja digitaalisten terveyspalveluiden käyttöä) kolmessa eri ajankohdassa (n= 163). Systemaattisella katsauksella kuvattiin pitkäaikais-sairaille nuorille kehitettyjä siirtymävaiheen digitaalisia terveysvalmennus elementtejä hyödyntäviä interventioita. Tutkimuksen tulokset osoittivat, että hyvä terveyteen liittyvä tietotaito oli yhteydessä alhaisempaan hoitoon liittyvään ahdistukseen lastensairaalassa. Itse arvioitu sairauden suurempi vaikutus elämään ja negatiiviset hoitokokemukset olivat yhteydessä suurempaan hoitoon liittyvään ahdistukseen siirtymän aikana. Luottamuksellisuudesta keskusteleminen ja lääkärin tapaaminen ilman vanhempia olivat siirtymävaiheen aikana puutteellisia. Luottamuksellisuuteen ja yksilölliseen hoitoon keskittymällä pystytään paremmin tunnistamaan eniten tukea tarvitsevat nuoret. Digitaalisten terveysinterventioiden tulisi olla hyvin integroituja hoitoprosessiin, helppokäyttöisiä, yksilöllisiä ja nuoria omahoitoon motivoivia. Tutkimuksen tulokset vahvistavat käsitystä siitä, että 12- vuoden iässä aloitetut, tavoitteelliset ja psykososiaalisen näkökulman sisältävät siirtymävaiheen interventiot voivat parantaa siirtymävaiheen hoitoa. Tulokset heijastavat yksilökeskeisen hoidon eri ulottuvuuksia sisältäen nuorten itse raportoimia sairauden vaikutuksia elämään, hoito-kokemuksia, hoitoon liittyvää ahdistusta, siirtymävalmiutta ja psykososiaalisia keskusteluja. Digitaaliset interventiot voivat tarjota pitkäaikaissairaille nuorille tehokasta ja helposti saavutettavaa lisäarvoa hoitoon. Terveysvalmennus on osoittanut positiivisia tuloksia ja voi olla keskeinen osa tulevaisuuden digitaalista terveydenhuoltoa. AVAINSANAT: nuoret, pitkäaikainen sairaus, siirtymävaihe, siirtymävalmius, digitaaliset terveyspalvelut, ahdistus, psykososiaalinen arviointi, terveysvalmennus